2016
DOI: 10.1159/000444122
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Assessment of Paclitaxel in Patients with Docetaxel-Resistant Esophageal Squamous Cell Carcinoma

Abstract: Background: Incomplete cross-resistances between paclitaxel (PTX) and docetaxel (DTX) has been demonstrated in several types of cancer. The objective of the present study was to assess the existence of cross-resistance between PTX and DTX in esophageal squamous cell carcinoma. Methods: Patients in the PTX group received PTX without DTX pretreatment, patients in the prior DTX (Pr-DTX) group received PTX after the development of resistance to DTX, and patients in the DTX group received DTX without subsequent PTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…These results are consistent with the reported moderate efficacy of a second, different taxane treatment in some patients presenting with various cancer types and who became refractory to a first taxane treatment, when paclitaxel and docetaxel were used sequentially in the same patients [ [13] , [14] , [15] , [16] ].…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with the reported moderate efficacy of a second, different taxane treatment in some patients presenting with various cancer types and who became refractory to a first taxane treatment, when paclitaxel and docetaxel were used sequentially in the same patients [ [13] , [14] , [15] , [16] ].…”
Section: Discussionsupporting
confidence: 88%
“…The rationale for enrollment of patients with prior docetaxel therapy in our study is supported by data showing that weekly paclitaxel is active in gastric cancer patients who had been refractory to docetaxel containing chemotherapy 22 . This indicates that cross‐resistance between docetaxel and paclitaxel in gastric cancer is incomplete 23‐25 . However, studies assessing the efficacy of taxane re‐exposure show inconsistent results, mainly because numbers of patients are small and in various treatment lines and analyses are mostly retrospective.…”
Section: Discussionmentioning
confidence: 79%
“…13 OS in both arms was comparable to the paclitaxel mono arm in western patients in the RAINBOW trial (5.9 months 200/398 patients), 7 underlying the poor 22 This indicates that cross-resistance between docetaxel and paclitaxel in gastric cancer is incomplete. [23][24][25] However, studies assessing the efficacy of taxane re-exposure show inconsistent results, mainly because numbers of patients are small and in various treatment lines and analyses are mostly retrospective. Our results regarding efficacy of taxane-rechallenge seem to be even worse than previous reports with a median survival of only 3.9 months in the paclitaxel control arm, which is close to those of patients who receive best supportive care only in second-and third-line setting (3.6-4.3 months).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ESCC, PTX monotherapy shows feasible efficacy, with an overall response rate of 44.2%, median duration of response of 4.8 months, and median OS of 10.4 months with manageable toxicity as a second-line regimen for patients previously treated with platinumbased chemotherapy [5]. Furthermore, it has also been reported that there is either no clinical cross-resistance or incomplete clinical cross-resistance between PTX and DOC in ESCC [23].…”
Section: Discussionmentioning
confidence: 99%